On Some Sandwich Results of Univalent Functions Related by Differential Operator - Theyab , Sarab Dakhil; Atshan , Waggas Galib; Abdullah , Habeeb Kareem (Iraqi Journal of Science, 2022)
Th goal of the pr s nt p p r is to obt in some differ tial sub rdin tion an sup r dination the rems for univalent functions related b differential operator Also, we discussed some sandwich-type results.